2020
DOI: 10.3390/brainsci10090586
|View full text |Cite
|
Sign up to set email alerts
|

Acute DOB and PMA Administration Impairs Motor and Sensorimotor Responses in Mice and Causes Hallucinogenic Effects in Adult Zebrafish

Abstract: The drastic increase in hallucinogenic compounds in illicit drug markets of new psychoactive substances (NPS) is a worldwide threat. Among these, 2, 5-dimetoxy-4-bromo-amphetamine (DOB) and paramethoxyamphetamine (PMA; marketed as “ecstasy”) are frequently purchased on the dark web and consumed for recreational purposes during rave/dance parties. In fact, these two substances seem to induce the same effects as MDMA, which could be due to their structural similarities. According to users, DOB and PMA share the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
2
6
0
Order By: Relevance
“…This time, from the comparison graphs of the maximum and average effects of all tested compounds, it is clear that 25I-NBOMe has a higher inhibitory effect ( Figures 4H,I ). Results are in accordance with previous studies conducted with other hallucinogenic substances, such as DOI ( 50 ) and 25I-NBOMe ( 37 ) on rats, Dimethoxybromoamphetamine (DOB), and Paramethoxyamphetamine (PMA) on mice ( 38 ). Evidence accumulated over the past 5 decades has indicated that the behavioral effects of hallucinogenic compounds are mediated by interactions with serotonin receptors in the brain ( 10 , 15 , 32 , 51 , 52 ), resulting in exceptionally strong behavioral and psychoactive properties in animals and humans ( 12 , 34 , 53 , 54 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This time, from the comparison graphs of the maximum and average effects of all tested compounds, it is clear that 25I-NBOMe has a higher inhibitory effect ( Figures 4H,I ). Results are in accordance with previous studies conducted with other hallucinogenic substances, such as DOI ( 50 ) and 25I-NBOMe ( 37 ) on rats, Dimethoxybromoamphetamine (DOB), and Paramethoxyamphetamine (PMA) on mice ( 38 ). Evidence accumulated over the past 5 decades has indicated that the behavioral effects of hallucinogenic compounds are mediated by interactions with serotonin receptors in the brain ( 10 , 15 , 32 , 51 , 52 ), resulting in exceptionally strong behavioral and psychoactive properties in animals and humans ( 12 , 34 , 53 , 54 ).…”
Section: Discussionsupporting
confidence: 92%
“…The effects of 25H-NBOMe, 25I-NBOMe, 25B-NBOMe, 2C-H, 2C-I, 2C-B, and LSD were investigated using a consolidated battery of behavioral tests routinely used in our laboratory for preclinical investigation of NPSs in rodents ( 38 , 42 , 43 ).…”
Section: Methodsmentioning
confidence: 99%
“…The effects of (±)cis-4,4 -DMAR, (±)trans-4,4 -DMAR and their co-administration were investigated by a protocol widely used in studies of "safety pharmacology" for the preclinical characterization of new molecules in rodents [106][107][108][109]. This protocol includes a series of observational behavioural tests carried out in a consecutive manner that monitor the animal responses up to 5 h after compound injections.…”
Section: Behavioural Studies: Physiological and Neuro-behavioural Responsesmentioning
confidence: 99%
“…In fact, tramadol, by increasing 5-HT levels, may induce visual alterations via the activation of serotonin receptors in the cortico-visual circuits [ 30 , 31 ]. In particular, the inhibition of both visual object and visual placing responses in rodents has been observed after the systemic administration of MDMA [ 32 ], DOB [ 33 ] or the potent serotoninergic agonist 25I-NBOMe [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this motor inhibition could possibly be due to either an anxiogenic effect of the molecule (stimulation of the noradrenergic fight-or-flight response) or as a consequence of the impaired visual and acoustic sensorimotor responses. In fact, the systemic administration of hallucinogenic phenethylamines that act as 5-HT receptor agonists, such as DOB, 2C-I and 25I-NBOMe [ 43 ], profoundly inhibits visual and acoustic sensorimotor responses in CD-1 mice, inducing a mild inhibition of spontaneous locomotion [ 33 ].…”
Section: Discussionmentioning
confidence: 99%